A Efetivação Dos Quadrinhos No Pnbe (2006-2014): Da Caixa Ao Leitor - Nascimento, Vanessa Yamaguti Do [UNIFESP] (2018)
Reading Is Considered A Human Right, However, In Brazilian Society, That Right Has Not Always Been Respected And It Might Not Even Be Respected Nowadays. On This Basis, The Brazilian Governments Try To Encourage And Guarantee Access To Books Through Public Policies. The Programa Nacional Biblioteca Da Escola (Pnbe) Was Created In 1997 (Fernandes, 2007; Paiva, 2012) With Ongoing Changes Since Its Creation. One Of The Changes Made Was The Insertion Of Comic Books Into School Libraries In 2006 (Vergueiro; Ramos, 2009). A Decade After This Introduction, We Have Tried To Prove Whether Or Not This Has Been Effective For The Pnbe By Examining The Use Of The Material In The School Environment. This Study Examined The Year Of Implementation Of Comic Books In Pnbe (2006) And The Final Year Of The Distribution Of Comic Books In Pnbe (2014). However This Programme Has Not Been Officially Closed By The Governments. The Field Research Was Carried Out In 2016, In The City Of Barueri " Located In The Metropolitan Region Of S